(untitled) (World Bulletin of Public Health, 2025)
Periodontal diseases, including gingivitis and periodontitis, are closely associated with the presence and quantity of specific periodontal pathogens. Rapid, sensitive, and specific detection of these microorganisms, including those difficult to culture, can be achieved using real-time PCR. In this study, subgingival plaque samples from healthy individuals and patients with gingivitis and periodontitis were collected and analyzed using the “ParodontoScreen” reagent kit to detect Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythensis, Treponema denticola, and Candida albicans. A. actinomycetemcomitans was most frequently detected in periodontitis patients (60.2%), significantly higher than in gingivitis patients (38%) and healthy individuals (5%). Other pathogens, including P. gingivalis, P. intermedia, T. forsythensis, and T. denticola, were also found more frequently and in higher quantities in diseased groups, with total bacterial load reaching up to 10^7 genome equivalents in periodontitis patients. Associations of pathogens, such as A. actinomycetemcomitans, P. gingivalis, and T. denticola, were common in both gingivitis and periodontitis patients, indicating the importance of microbial interactions in disease progression. These findings emphasize the significance of quantifying periodontal pathogens and their associations for predicting disease progression and guiding appropriate therapeutic interventions, with real-time PCR serving as a reliable tool for detecting species contributing to periodontal tissue destruction.